Arsenic trioxide dose capping to decrease toxicity in the treatment of acute promyelocytic leukemia. (September 2022) - Zacholski, Kyle; Hambley, Bryan; Hickey, Erin; Kashanian, Sarah; Li, Andrew; Baer, Maria R; Duong, Vu H; Newman, Matthew J; DeZern, Amy; Gojo, Ivana; Smith, B Douglas; Levis, Mark J; et al.
Arsenic trioxide (ATO) and all-trans retinoic acid (ATRA) combination therapy yields high complete remission and disease-free survival rates in acute promyelocytic leukemia (APL). ATO is dosed on actual body weight and high ATO doses in overweight patients may contribute to increased toxicity. We performed a retrospective, two-center study comparing toxicities in patients who received the Lo-Coco et al ATRA/ATO regimen with capped ATO, ≤10 mg/dose, and non-capped ATO, >10 mg/dose. A total of 44 patients were included; 15 received doses ≤10 mg and 29 received >10 mg. During induction, there was no difference in the incidence of grade ≥3 hepatotoxicity, grade ≥3 QTc prolongation, neurotoxicity, and cardiac toxicity between groups. In consolidation, patients receiving >10 mg/dose experienced a greater incidence of neurotoxicity (66.7% vs 22.2%; p = 0.046). Capping doses saved $24634.37/patient and reduced waste of partially-used vials. At a median follow-up of 27 months, no disease relapses occurred in either group. This represents an opportunity to improve the safety profile of this highly effective regimen.